Gestión técnica de riesgos laborales en los talleres de mecánica automotriz de la Unidad Educativa Carlos Cisneros de la ciudad de Riobamba. - Damián Lemache, Mariela Catherine (2024)
This research study arose from the need to prevent occupational hazards in the B1-B2 workshops of the automotive mechanics course at the Carlos Cisneros Educational Unit, to avoid work-related accidents and occupational illnesses. The technical management of occupational risks was carried out in three stages: (1) identification of risk factors through onsite visits to each of the workstations, by applying a checklist for each of the seven workstations; (2) evaluation using three methodologies: (a) General Evaluation Method of Occupational Risks proposed by the National Institute for Safety and Health at Work (INSST), (b) Technical Prevention Note NTP 330: Simplified System of accident risk assessment and (c) Mathematical Risk Assessment Method by William T. Fine; and (3) Finally, to give an overview of the risk factors at each of the seven workstations, a checklist was applied to each of the seven workstations. Fine and (3) finally, to fulfill the proposed objectives, a manual on Health and Safety at Work was drawn up as a proposal for prevention and control. The results of the research revealed that the student's position presented the greatest exposure, with mechanical risk factors being the most predominant. The workshop coordinator's job had the lowest exposure, with 18 risk factors identified, compared to the 25 factors identified for the student job. Based on this information, a manual of preventive measures was drawn up for the control of risk factors, focusing on the source, means of transmission, and receptor, to create a safe working environment for those who use the workshops at the Carlos Cisneros Educational Unit.